A noção de acontecimento na experiência do DOCTV RN IV Sangue do Barro - Cardoso, Ana Tázia Patrício de Melo (2012)
This dissertation presents a reflection upon the notion of event, inspired by the contributions of Edgar Morin to the thinking of the present. The research analysis this notion particularly from the experience of the documentary titled Sangue do Barro, which was the winner of the 4th edition of DOCTV, in the federal state of Rio Grande do Norte in 2008. The study focuses on how facts from daily life can be approached by the documentary making process, and how in this process the questioning of facts leads to the questioning of social realities. In this perspective, through the illustrative case of Sangue do Barro, the research develops the hypothesis of how in the documentary process, which aims at revealing a particular history, is the revealing of the particular able to reflect the universal. The dissertation thus assumes this situation as precisely the configuration of the sociology of present, proposed by Edgar Morin. Furthermore, along with the theoretical premises of the sociology of the present, the research performs a brief historical analysis of documentary practices, Brazilian audiovisual public policies, and it also discusses the technical contributions of several contemporary film makers and contemporary thinkers, such as Jean Rouch, Bill Nichols, Ismail Xavier, Consuelo Lins, Gilles Lipovetsky, Jean Serroy, Michel Foucault, Alfredo Pena-Vega, Nicole Lapierre, etc